ANALYSIS OF RELATIONSHIP BETWEEN TIDAL SEA WITH SEDIMENTATION (Case Study: Port Container Wharf Surabaya) - Yuwono, Yuwono; Qhomariyah, Lailatul (Departemen Teknik Geomatika ITS, 2016)
Indonesian archipelagohas a high necessity of sea transportationtosupport the trade activities andmobility between one island and another. The harbor security is an important factortoensure the safety ofthe ships which are being leant there, therefore the sedimentation is neededto be observed in order to find out the changes of sedimentationso that theshipwould notrun aground. The formation ofsedimentationinthe dockis influencedby several factors, one of them istidal.Domesticdockcontainer portof Surabayais onethe docks that facilitatesdockshipsat the jettyport inEastJava. To observe the influence ofthe tides to thedock sedimentation, it is necessary to knowthe changesofsedimentation, so thesecurity of the shipsthat willbe dock could be guaranteed.The results of this study was finding theimpacts of tidal phenomena to the sediment formed in the domestic dock container port Surabaya we can conclude that when the Formzahl number is greater than the previous year, the sedimentation volume will also increase. The sedimentation volume in 2011 amounted to 9,460 m3 with Formzahl numbers of 0.662 is used as the reference to a sedimentation volume increasing in 2012 amounted to 49,537 m3 with formzahl number of 0.819. The increasing formzahl numbers which also means increase in the phenomenon of ebb and flow of sea water, has shown a difference of sedimentation volume from 2011 to 2012 amounted to 40,077 m3. And In the sedimentation volume in 2013 amounted to 14,306 m3 with a formzahl number of 0.722 is used as the reference to an increase in sedimentation volume in 2014 amounted to 35,102 m3 with formzahl number of 0.758. The increasing formzahl numbers which also means an increase in the phenomenon of ebb and flow of sea water which has resulted in a difference of sedimentation volume from 2013 to 2014 amounted to 20,796 m3.